Injection Snoreplasty- A Simple Treatment for Habitual Snoring - Bakshi Jaimanti; Gupta K. Ashok; Dash K. Anil; Khandelwal Gaurav (Highlights on Medicine and Medical Research Vol. 15, 2021)
Aims: Injection snoreplasty was recently introduced as a safe, effective, and minimally invasive treatment for primary snoring. We assess the effectiveness of the treatment in our patients. Simple snoring can occur due to deviated nasal septum, mass in nasopharynx or in the nasal cavities, excessive palatal flutter and bulky base of tongue. Study Design: It was a prospective, non-randomised study on 54 patients with primary snoring. Place and Duration of Study: Study was done in the department of otolaryngology &head neck surgery at PGIMER, Chandigarh, India over 7 years between January 2004 and December 2010. Methodology: Patients were questioned about their symptoms; a detailed clinical and radiological examination was done in all patients. All the causes of snoring were ruled out. 1-3% sodium tetradecyl sulphate (STS) injection was administered in all patients in 1-3 sittings. Patients were assessed after 1, 3 and 6 months and their improvement was noted Results: There were 47 males and 7 females enrolled in our study with mean age as 47.6 years. The mean duration of snoring was 76.1 months. The average BMI of patients was 28.11. All the patients except 4 were initially injected 1% STS injection; the others were injected 3%. 11 patients were re-injected at 1 month and 4 had 2nd re-injection at 3 month follow up. The mean improvement in symptoms was 57.24%. The only side effect was pain which in majority of patients was mild. There was no correlation between BMI and percentage of improvement. Conclusion: Injection snoreplasty is a safe and cost effective treatment for primary snoring.